A dichloromethane-resistant VOCs recovery organic membrane and preparation method thereof

By using PVDF film as the base film in the organic film and introducing porous HOF material HIAM-JM and PBI solutions to form a multi-layer film structure, the problem of insufficient corrosion resistance performance of existing films when treating dichloromethane is solved, and efficient VOCs recovery and film flux are achieved.

CN119733387APending Publication Date: 2025-04-01JIANGSU JIUMO HIGH TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411984979.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing organic films have insufficient corrosion resistance when dealing with strong polar solvents such as dichloromethane, and the PDMS films are prone to sacrifice membrane flux while ensuring separation performance, which cannot meet the actual needs of industrialization.

Method used

The PVDF film is used as the base film, and a multi-layer film structure is formed by introducing porous HOF material HIAM-JM into the film, combining PBI solution and PDMS to improve the film's recovery performance on dichloromethane and break through the trade-off effect.

Benefits of technology

It achieves the improvement of membrane separation performance while ensuring membrane flux, and has extremely strong corrosion resistance to dichloromethane, extends the service life of the membrane, and improves the VOCs recovery efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733387A_ABST
    Figure CN119733387A_ABST
Patent Text Reader

Abstract

The present invention discloses a dichloromethane-resistant VOCs recovery organic membrane and a preparation method thereof, wherein the organic membrane comprises a base membrane layer, an intermediate layer and an active layer arranged in sequence, wherein the base membrane layer is polyvinylidene fluoride, the intermediate layer is polybenzimidazole dispersed with a hydrogen-bonded organic framework material, and the active layer is cross-linked polydimethylsiloxane. The present invention adopts a PVDF membrane with extremely strong corrosion resistance to organic solvents as a base membrane, improves the recovery performance of the membrane for dichloromethane by using a porous HOF material, assists PDMS in breaking through the trade-off effect, and improves the membrane separation performance without reducing the membrane flux.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of VOCs recovery membrane separation, and specifically relates to a dichloromethane-resistant VOCs recovery organic membrane and a preparation method thereof. Background Art

[0002] Dichloromethane is a common industrial solvent that can be used as a raw material for synthetic rubber and plastics. In the past, it was often used to produce products such as polyvinyl chloride plastics and chloroprene rubber. In the pharmaceutical field, dichloromethane is often used as a drug intermediate to synthesize antibiotics and antimalarial drugs, so pharmaceutical companies often produce a large amount of dichloromethane waste gas. In recent years, chip and new energy companies have developed rapidly. Dichloromethane, as an excellent solvent, can be used to clean electronic components, printed circuit boards, and in the production process of lithium battery separators and liquid crystal displays. Therefore, how to recycle and treat high-content dichloromethane waste gas has become an urgent key issue.

[0003] As one of the emerging separation and recovery technologies, membrane separation technology has the advantages of small footprint and no additional by-products. However, conventional organic membrane materials are not resistant to strong polar solvents, so PVDF and other materials resistant to organic solvents are needed as base membrane materials. PDMS membrane has broad application prospects in the separation and recovery of volatile organic compounds (VOCs). Its preferential permeability to organic matter can make it widely used in the field of VOCs recovery, but PDMS membrane is susceptible to the trade-off effect, that is, most of the membrane flux must be sacrificed while ensuring high separation performance. If the separation membrane flux is large enough, the separation performance of the membrane cannot be guaranteed. Therefore, how to break through the trade-off effect of PDMS membrane so that it can meet the actual needs of industrialization and avoid the loss of permeation flux while ensuring membrane separation performance has become a hot topic in the field of membrane materials research.

[0004] In recent years, the development of porous framework materials has been extremely rapid. With the continuous derivation and expansion of MOF and COF materials, tens of thousands of porous framework materials have been applied to different directions such as gas separation, liquid separation, and chemical catalysis. Hydrogen-bonded organic framework materials (HOF) have become one of the porous materials that are currently receiving more attention because of their low bonding energy requirements, rich and controllable pores, and strong plasticity and resilience during use. However, most porous framework materials will encounter problems such as being unable to tolerate the separation system, large amounts of porous framework materials deposited to block the membrane pores, and the collapse of the pores of the porous framework materials during use, which will affect the overall service life of the separation membrane. Summary of the invention

[0005] In view of the above problems, the present invention provides a dichloromethane-resistant VOCs recovery organic membrane and a preparation method thereof. The present invention adopts a PVDF membrane with extremely strong corrosion resistance to organic solvents as a base membrane, improves the dichloromethane recovery performance of the membrane by using a porous HOF material, assists PDMS in breaking through the trade-off effect, and improves the membrane separation performance without reducing the membrane flux.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] A dichloromethane-resistant VOCs recovery organic membrane comprises a base membrane layer, an intermediate layer and an active layer arranged in sequence, wherein the base membrane layer is polyvinylidene fluoride, the intermediate layer is polybenzimidazole dispersed with a hydrogen bond organic framework material, and the active layer is cross-linked polydimethylsiloxane.

[0008] Preferably, the base film further comprises a support layer, and the support layer is a non-woven fabric.

[0009] Preferably, the hydrogen-bonded organic framework material (HOF) is HIAM-JM, and the HIAM-JM is prepared by the following method:

[0010] 2,2-Dithiodibenzoic acid and acetic acid were evenly dispersed in a ratio of 0.05-0.1 g: 50-80 mL, and then reacted at 70-90 °C for 10-14 h under vacuum conditions to obtain HIAM-JM. The product, a light yellow solid, is HIAM-JM, which is an unactivated HOF material and needs to be activated by high temperature treatment.

[0011] Preferably, the method for preparing HIAM-JM further comprises the step of washing the product with acetic acid.

[0012] Preferably, the hydrogen-bonding organic framework material is activated.

[0013] Preferably, the average particle size of the hydrogen-bonded organic framework material is 30-50 nm.

[0014] Preferably, the thickness of the intermediate layer is 70-80 μm, and the thickness of the active layer is 60-90 μm.

[0015] The present invention further provides a method for preparing the above-mentioned dichloromethane-resistant VOCs recovery organic film, comprising the following steps:

[0016] The first coating liquid is applied on the base film, and after pre-drying, the second coating liquid is applied thereon, and then cross-linked at high temperature to obtain;

[0017] The first coating liquid is prepared by the following method: ultrasonically oscillating a hydrogen-bonded organic framework material in n-heptane to obtain a HOF dispersion, and then uniformly mixing the HOF dispersion with a polybenzimidazole (PBI) solution to obtain the first coating liquid;

[0018] The second coating liquid is prepared by the following method: uniformly mixing a n-heptane solution of hydroxy vinyl silicone oil with a crosslinking agent and a catalyst to react, thereby obtaining the second coating liquid.

[0019] Preferably, the pre-drying temperature is 80-100°C.

[0020] Preferably, the pre-drying time is 0.5 to 1 hour.

[0021] Preferably, the high temperature crosslinking temperature is 120-140°C.

[0022] Preferably, the high temperature cross-linking time is 4 to 6 hours. After high temperature cross-linking, a dichloromethane-resistant VOCs recovery organic membrane is obtained, and the HOF also completes the activation process during the high temperature process.

[0023] Preferably, in the method for preparing the first coating solution, the mass ratio of the hydrogen-bonding organic framework material to n-heptane is 2-10:90-98.

[0024] Preferably, in the method for preparing the first coating solution, the solvent of the polybenzimidazole solution is DMAc. More preferably, in the polybenzimidazole solution, the mass ratio of polybenzimidazole to DMAc is 20-25:75-80.

[0025] Preferably, in the method for preparing the first coating solution, the mass ratio of the polybenzimidazole solution to the HOF dispersion is 5-10:90-95.

[0026] Preferably, in the preparation method of the second coating liquid, the mass ratio of hydroxy vinyl silicone oil to n-heptane is 7-12:88-93.

[0027] Preferably, in the method for preparing the second coating liquid, the mass ratio of the crosslinking agent to the n-heptane solution of the hydroxy vinyl silicone oil is 1-4:6-9.

[0028] Preferably, in the method for preparing the second coating liquid, the catalyst is 0.01-1% by weight of a n-heptane solution of hydroxy vinyl silicone oil.

[0029] Preferably, the cross-linking agent is tetraethoxysilane (TEOS), and the catalyst is tetrabutyltin.

[0030] Preferably, the viscosity of the second coating liquid is 18 mPa·s.

[0031] Preferably, the base film is prepared by the following method: a solution of polyvinylidene fluoride is uniformly coated on a non-woven fabric, and then the base film is obtained through a phase inversion process.

[0032] Preferably, the phase inversion method is: immersion in water.

[0033] Preferably, the coating thickness of the polyvinylidene fluoride solution is 140-160 μm.

[0034] Preferably, the solvent of the polyvinylidene fluoride solution is DMAc, DMF or NMP.

[0035] Preferably, the mass ratio of polyvinylidene fluoride to solvent in the polyvinylidene fluoride solution is 18-23:77-82.

[0036] The beneficial effects of the present invention are:

[0037] The present invention provides a dichloromethane-resistant VOCs recovery organic membrane and a preparation method thereof. The present invention adopts a PVDF membrane with extremely strong corrosion resistance to organic solvents as a base membrane, improves the dichloromethane recovery performance of the membrane by using a porous HOF material, assists PDMS in breaking through the trade-off effect, and improves the membrane separation performance without reducing the membrane flux.

[0038] The HOF material HIAM-JM used has been proven through experimental tests to have extremely strong corrosion resistance to dichloromethane, which can help the PDMS membrane break through the trade-off effect (i.e., the permeation flux will be greatly reduced while ensuring higher separation performance).

[0039] The HOF material used in the present invention has extremely strong solvent resistance and can maintain the stability of its porous structure when immersed in pure dichloromethane. Because its hydrogen bond formation energy is lower than that of MOF and COF, its structure has strong diversity and recovery.

[0040] PBI solution was added to the coating liquid of HOF material. One of the reasons is that for previous membrane materials, directly coating small molecule framework materials can easily cause the framework materials to block the membrane pores and the porous framework materials can easily collapse and fail during use. PBI solution can self-polymerize to form a mesh structure when the solution evaporates under high temperature conditions, which acts as a thin net to prevent excessive penetration and aggregation of HOF from blocking the membrane pores. At the same time, because PBI has imidazole groups, it has good interfacial compatibility with organic materials and can undergo chemical cross-linking, so it also has the function of supporting and fixing HOF. When PBI is cross-linked under high temperature conditions, the activation process of HOF is also completed, and the excess solvent in the HOF pores is removed, which improves the overall efficiency of the membrane making process. After the first coating, PDMS is applied for the second coating, which can achieve the separation of VOCs on the one hand and further fix the HOF material on the other hand. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the XRD comparison diagram of HIAM-JM after being immersed in dichloromethane and placed in air for different time periods. DETAILED DESCRIPTION

[0042] The present invention is further explained below in conjunction with the examples. The following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0043] Example 1

[0044] (1) Polyvinylidene fluoride was dissolved in DMAc solvent at 70°C, with a mass ratio of PVDF to solvent of 18:82. After complete dissolution, it was allowed to stand and cool to degas, and then evenly coated on a non-woven fabric with a coating thickness of 140 μm. After coating, it was immediately immersed in pure water to complete the base film phase transformation process, thereby obtaining a PVDF base film, which was then stored in pure water.

[0045] (2) Add 2,2-dithiodibenzoic acid and acetic acid to the polytetrafluoroethylene liner of a 100mL hydrothermal kettle, with the ratio of 0.05g: 80mL. After adding, place the polytetrafluoroethylene liner in an ultrasonic oscillation until the drugs are evenly dispersed in the acetic acid solution. After ensuring that the dispersion is even, load the polytetrafluoroethylene into the hydrothermal kettle, place the hydrothermal kettle in a vacuum oven, and react at 70°C for 10 hours to prepare HIAM-JM (HOF) by solvent thermal synthesis. After the reaction time is over, wait for the hydrothermal kettle to cool to room temperature, filter the solid in the polytetrafluoroethylene liner with filter paper, and then wash it with fresh acetic acid solution 3 times. After washing, filter it again with filter paper. The light yellow solid obtained is HIAM-JM. This solid is the HOF material that has not been activated yet, and it needs to be activated by high temperature treatment.

[0046] (3) Dissolving polybenzimidazole (PBI) in DMAc at 70° C. with a mass ratio of PBI to DMAc of 20:80. After complete dissolution, standing to cool and degas, thereby obtaining a PBI solution.

[0047] (4) The HIAM-JM solid obtained in step (2) is added to n-heptane, with the mass ratio of HIAM-JM to n-heptane being 2:98. After the addition, ultrasonic vibration is used to uniformly disperse the HIAM-JM in the n-heptane to obtain a HIAM-JM liquid.

[0048] (5) The PBI solution of step (3) and the HIAM-JM liquid of step (4) are mixed evenly under magnetic stirring, the mass ratio of the PBI solution to the HIAM-JM liquid being 5:95, and the coating liquid 1 is obtained after mixing evenly.

[0049] (6) Dissolve hydroxy vinyl silicone oil in n-heptane at room temperature, with the mass ratio of hydroxy vinyl silicone oil to n-heptane being 7:93, to obtain a uniform hydroxy vinyl silicone oil solution. Add crosslinking agent tetraethoxysilane (TEOS) to the uniform hydroxy vinyl silicone oil solution, with the mass ratio of the added amount of the crosslinking agent to the hydroxy vinyl silicone oil solution being 1:9, and stir evenly at room temperature. Add catalyst tetrabutyltin to the mixed solution, with the added amount of the catalyst being 0.01% of the weight of the hydroxy vinyl silicone oil solution. After the addition is completed, stir the reaction at room temperature, and stop stirring when the viscosity of the mixed solution after adding the catalyst reaches 18 mPa·s, to obtain coating liquid 2.

[0050] (7) The coating solution 1 obtained in step (5) is coated on the PVDF base film obtained in step 1, and the coating thickness is 70 μm. After coating, the composite film is placed in an oven for pre-drying at 80° C. for 0.5 h to complete the first coating of the composite film.

[0051] (8) After the composite membrane coated for the first time in step (7) is placed at room temperature, the coating solution 2 obtained in step (6) is coated on its surface, and the coating thickness is 60 μm. After coating, it is placed in an oven at 120°C for crosslinking for 4 hours. After high-temperature crosslinking, a dichloromethane-resistant VOCs recovery organic membrane is obtained, and the HIAM-JM also completes the activation process during the high-temperature process.

[0052] Example 2

[0053] (1) Polyvinylidene fluoride is dissolved in DMF solvent at 80°C, with the mass ratio of PVDF to solvent being 20:80. After being completely dissolved, it is allowed to stand and cool to degas, and then evenly coated on a non-woven fabric with a coating thickness of 150 μm. After coating, it is immediately immersed in pure water to complete the base film phase transformation process, thereby obtaining a PVDF base film, which is then stored in pure water.

[0054] (2) Add 2,2-dithiodibenzoic acid and acetic acid to the polytetrafluoroethylene liner of a 100mL hydrothermal kettle in a ratio of 0.06g:75mL. After adding, place the polytetrafluoroethylene liner in an ultrasonic oscillation until the drugs are evenly dispersed in the acetic acid solution. After ensuring that the dispersion is even, load the polytetrafluoroethylene into the hydrothermal kettle, place the hydrothermal kettle in a vacuum oven, and react at 80°C for 11 hours to prepare HIAM-JM (HOF) by solvent thermal synthesis. After the reaction time is over, wait for the hydrothermal kettle to cool to room temperature, filter the solid in the polytetrafluoroethylene liner with filter paper, and then wash it with fresh acetic acid solution 3 times. After washing, filter it again with filter paper. The light yellow solid obtained is HIAM-JM. This solid is an unactivated HOF material and needs to be activated by high temperature treatment.

[0055] (3) Dissolving polybenzimidazole (PBI) in DMAc at 80° C. with a mass ratio of PBI to DMAc of 21:79. After complete dissolution, standing to cool and degas, thereby obtaining a PBI solution.

[0056] (4) The HIAM-JM solid obtained in step (2) is added to n-heptane, with the mass ratio of HIAM-JM to n-heptane being 3:97. After the addition, ultrasonic vibration is used to evenly disperse the HIAM-JM in the n-heptane to obtain a HIAM-JM liquid.

[0057] (5) The PBI solution of step (3) and the HIAM-JM liquid of step (4) are mixed evenly under magnetic stirring, the mass ratio of the PBI solution to the HIAM-JM liquid being 6:94. After mixing evenly, a coating liquid 1 is obtained.

[0058] (6) Dissolve hydroxy vinyl silicone oil in n-heptane at room temperature, with the mass ratio of hydroxy vinyl silicone oil to n-heptane being 8:92, to obtain a uniform hydroxy vinyl silicone oil solution. Add crosslinking agent tetraethoxysilane (TEOS) to the uniform hydroxy vinyl silicone oil solution, with the mass ratio of the added amount of the crosslinking agent to the hydroxy vinyl silicone oil solution being 2:8, and stir evenly at room temperature. Add catalyst tetrabutyltin to the mixed solution, with the added amount of the catalyst being 0.04% of the weight of the hydroxy vinyl silicone oil solution. After the addition is completed, stir the reaction at room temperature, and stop stirring when the viscosity of the mixed solution after adding the catalyst reaches 18 mPa·s, to obtain coating liquid 2.

[0059] (7) The coating solution 1 obtained in step (5) is coated on the PVDF base film obtained in step 1, and the coating thickness is 75 μm. After coating, the composite film is placed in an oven for pre-drying at 90° C. for 0.6 h to complete the first coating of the composite film.

[0060] (8) After the composite membrane coated for the first time in step (7) is placed at room temperature, the coating solution 2 obtained in step (6) is coated on its surface, and the coating thickness is 70 μm. After coating, it is placed in an oven at 130°C for crosslinking for 5 hours. After high-temperature crosslinking, a dichloromethane-resistant VOCs recovery organic membrane is obtained, and the HIAM-JM also completes the activation process during the high-temperature process.

[0061] Example 3

[0062] (1) Polyvinylidene fluoride is dissolved in NMP solvent at 70-90°C, with the mass ratio of PVDF to solvent being 20:80. After being completely dissolved, it is allowed to stand and cool to degas, and then evenly coated on a non-woven fabric with a coating thickness of 150 μm. After coating, it is immediately immersed in pure water to complete the base film phase transformation process, thereby obtaining a PVDF base film, which is then stored in pure water.

[0063] (2) Add 2,2-dithiodibenzoic acid and acetic acid to the polytetrafluoroethylene liner of a 100mL hydrothermal kettle, with the ratio of 0.08g: 50mL. After adding, place the polytetrafluoroethylene liner in an ultrasonic oscillation until the drugs are evenly dispersed in the acetic acid solution. After ensuring that the dispersion is even, load the polytetrafluoroethylene into the hydrothermal kettle, place the hydrothermal kettle in a vacuum oven, and react at 80°C for 12 hours to prepare HIAM-JM (HOF) by solvent thermal synthesis. After the reaction time is over, wait for the hydrothermal kettle to cool to room temperature, filter the solid in the polytetrafluoroethylene liner with filter paper, and then wash it with fresh acetic acid solution 3 times. After washing, filter it again with filter paper. The light yellow solid obtained is HIAM-JM. This solid is the HOF material that has not been activated yet, and it needs to be activated by high temperature treatment.

[0064] (3) Dissolving polybenzimidazole (PBI) in DMAc at 80°C with a mass ratio of PBI to DMAc of 23:77. After complete dissolution, the solution was allowed to stand to cool and degas, thereby obtaining a PBI solution.

[0065] (4) The HIAM-JM solid obtained in step (2) is added to n-heptane, with the mass ratio of HIAM-JM to n-heptane being 8:92. After the addition, ultrasonic vibration is used to uniformly disperse the HIAM-JM in the n-heptane to obtain a HIAM-JM liquid.

[0066] (5) The PBI solution of step (3) and the HIAM-JM liquid of step (4) are mixed evenly under magnetic stirring, the mass ratio of the PBI solution to the HIAM-JM liquid being 8:92. After mixing evenly, a coating liquid 1 is obtained.

[0067] (6) Dissolve hydroxy vinyl silicone oil in n-heptane at room temperature, with the mass ratio of hydroxy vinyl silicone oil to n-heptane being 10:90, to obtain a uniform hydroxy vinyl silicone oil solution. Add crosslinking agent tetraethoxysilane (TEOS) to the uniform hydroxy vinyl silicone oil solution, with the mass ratio of the added amount of the crosslinking agent to the hydroxy vinyl silicone oil solution being 3:7, and stir evenly at room temperature. Add catalyst tetrabutyltin to the mixed solution, with the added amount of the catalyst being 0.08% by weight of the hydroxy vinyl silicone oil solution. After the addition is completed, stir the reaction at room temperature, and stop stirring when the viscosity of the mixed solution after adding the catalyst reaches 18 mPa·s, to obtain coating liquid 2.

[0068] (7) The coating solution 1 obtained in step (5) is coated on the PVDF base film obtained in step 1, and the coating thickness is 75 μm. After coating, the composite film is placed in an oven for pre-drying at 90° C. for 0.8 h to complete the first coating of the composite film.

[0069] (8) After the composite membrane coated for the first time in step (7) is placed at room temperature, the coating solution 2 obtained in step (60) is coated on its surface, and the coating thickness is 80 μm. After coating, the composite membrane is placed in an oven at 130° C. for crosslinking for 5 h. After high-temperature crosslinking, a dichloromethane-resistant VOCs recovery organic membrane is obtained, and the HIAM-JM also completes the activation process during the high-temperature process.

[0070] Example 4

[0071] (1) Polyvinylidene fluoride is dissolved in DMAc solvent at 90°C, with a mass ratio of PVDF to solvent of 23:77. After complete dissolution, it is allowed to stand and cool to degas, and then evenly coated on a non-woven fabric with a coating thickness of 160 μm. After coating, it is immediately immersed in pure water to complete the base film phase transformation process, thereby obtaining a PVDF base film, which is then stored in pure water.

[0072] (2) Add 2,2-dithiodibenzoic acid and acetic acid to the polytetrafluoroethylene liner of a 100mL hydrothermal kettle in a ratio of 0.1g:80mL. After adding, place the polytetrafluoroethylene liner in an ultrasonic oscillation until the drugs are evenly dispersed in the acetic acid solution. After ensuring that the dispersion is even, load the polytetrafluoroethylene into the hydrothermal kettle, place the hydrothermal kettle in a vacuum oven, and react at 90°C for 14 hours to prepare HIAM-JM (HOF) by solvent thermal synthesis. After the reaction time is over, wait for the hydrothermal kettle to cool to room temperature, filter the solid in the polytetrafluoroethylene liner with filter paper, and then wash it with fresh acetic acid solution 3 times. After washing, filter it again with filter paper. The light yellow solid obtained is HIAM-JM. This solid is an unactivated HOF material and needs to be activated by high temperature treatment.

[0073] (3) Dissolve polybenzimidazole (PBI) in DMAc at 90°C with a mass ratio of PBI to DMAc of 25:75. After complete dissolution, let stand to cool and degas to obtain a PBI solution.

[0074] (4) The HIAM-JM solid obtained in step (2) is added to n-heptane, with the mass ratio of HIAM-JM to n-heptane being 10:90. After the addition, ultrasonic vibration is used to uniformly disperse the HIAM-JM in the n-heptane to obtain a HIAM-JM liquid.

[0075] (5) The PBI solution of step (3) and the HIAM-JM liquid of step (4) are mixed evenly under magnetic stirring, wherein the mass ratio of the PBI solution to the HIAM-JM liquid is 10:90. After mixing evenly, a coating liquid 1 is obtained.

[0076] (6) Dissolve hydroxy vinyl silicone oil in n-heptane at room temperature, with the mass ratio of hydroxy vinyl silicone oil to n-heptane being 12:88, to obtain a uniform hydroxy vinyl silicone oil solution. Add crosslinking agent tetraethoxysilane (TEOS) to the uniform hydroxy vinyl silicone oil solution, with the mass ratio of the added amount of the crosslinking agent to the hydroxy vinyl silicone oil solution being 4:6, and stir evenly at room temperature. Add catalyst tetrabutyltin to the mixed solution, with the added amount of the catalyst being 1% of the weight of the hydroxy vinyl silicone oil solution. After the addition is completed, stir the reaction at room temperature, and stop stirring when the viscosity of the mixed solution after adding the catalyst reaches 18 mPa·s, to obtain coating liquid 2.

[0077] (7) The coating solution 1 obtained in step (5) is coated on the PVDF base film obtained in step 1, and the coating thickness is 80 μm. After coating, the composite film is placed in an oven and pre-dried at 100° C. for 1 h to complete the first coating of the composite film.

[0078] (8) After the composite membrane coated for the first time in step (7) is placed at room temperature, the coating solution 2 obtained in step (6) is coated on its surface, and the coating thickness is 90 μm. After coating, it is placed in an oven at 140°C for crosslinking for 6 hours. After high-temperature crosslinking, a dichloromethane-resistant VOCs recovery organic membrane is obtained, and the HIAM-JM also completes the activation process during the high-temperature process.

[0079] Example 5

[0080] The membrane materials prepared in Examples 1 to 4 were subjected to pervaporation performance tests, oxygen separation performance tests, and dichloromethane gas separation performance tests, and the HIAM-JM material of Example 3 was subjected to an XRD test after long-term dichloromethane immersion. The results are as follows:

[0081] (1) Permeation gasification test before and after immersion in dichloromethane for 30 days:

[0082] The composite membranes prepared in Examples 1 to 4 and the common PDMS membranes were tested for membrane separation performance on a self-designed pervaporation experimental platform. The experiments used 5% ethanol water as the raw material, the experimental temperature was 40°C, the vacuum degree was 2000 Pa, and the membrane area used was 0.089 m 2 The experimental results are shown in Table 1.

[0083] Table 1 Test results of the composite membrane separation performance affected by dichloromethane

[0084]

[0085] The results of the ethanol-water pervaporation test show that the PDMS membrane modified with HIAM-JM material can improve the overall dichloromethane resistance of the membrane and can increase the permeation flux of the membrane to a certain extent.

[0086] (2) Gas separation pilot test:

[0087] The composite membranes prepared in Examples 1 to 4 and ordinary PDMS membranes were tested for their separation performance on a self-designed gas separation experimental platform. Compressed air, dichloromethane volatile gas, and N2 were used to evaluate the tolerance of the composite membranes to dichloromethane and their separation performance for dichloromethane. The gas test pressure was 0.45 MPa, the test environment temperature was 30°C, and the membrane area used was 0.089 m 2 The experimental results are shown in Table 2.

[0088] Table 2 Test results of air gas separation performance affected by dichloromethane

[0089]

[0090] Since the PDMS membrane has the ability to separate O2 in the air, the effect of dichloromethane on the membrane separation performance can be judged by the O2 concentration on the permeate side before and after the membrane is soaked in dichloromethane. From the data in Table 2, it can be seen that before and after soaking in dichloromethane, the gas flux of Examples 3 and 4 changes very little and the permeate oxygen concentration does not change, so it can be proved that this composite membrane has strong corrosion resistance to dichloromethane.

[0091] The dichloromethane separation performance test was carried out, and the test results are shown in Table 3

[0092] Table 3 Dichloromethane separation performance test results

[0093]

[0094] The single-component gas flux test can determine the separation performance of the separation membrane for dichloromethane. From the data in Table 3, it can be seen that the separation ratio of dichloromethane / N2 of the ordinary PDMS membrane is only 6.36, while the separation ratio of dichloromethane / N2 of Example 3 can reach 21.85, and the performance has been greatly improved.

[0095] (3) Long-term dichloromethane resistance test of HIAM-JM material of Example 3:

[0096] The activated HIAM-JM material was subjected to XRD testing to obtain the characteristic peaks of this hydrogen-bonded organic framework material. The activated HIAM-JM material was then placed in air and immersed in dichloromethane liquid, and XRD analysis was performed by sampling at different times to determine whether the material had structural collapse. Figure 1From the XRD diagram, we can see that the characteristic peaks of the HIAM-JM material have not changed after being placed in the air for 3 years; the characteristic peaks of the HIAM-JM material have not changed after being immersed in dichloromethane for 2 years. After immersion for 3 years, the peak intensity of a small number of characteristic peaks decreased, but there are still peaks, which means that its main framework has not collapsed significantly and its performance is still good.

[0097] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, making several substitutions or obvious modifications without departing from the concept of the present invention, and having the same performance or use, should be regarded as belonging to the protection scope of the present invention.

Claims

1. A dichloromethane-resistant VOCs recovery organic membrane, characterized in that: The invention comprises a base film layer, an intermediate layer and an active layer which are arranged in sequence. The base film layer is polyvinylidene fluoride, the intermediate layer is polybenzimidazole dispersed with hydrogen bond organic framework material, and the active layer is cross-linked polydimethylsiloxane.

2. The dichloromethane-resistant VOCs recovery organic membrane according to claim 1, characterized in that: The hydrogen-bonded organic framework material is HIAM-JM; the hydrogen-bonded organic framework material is activated, and the HIAM-JM is prepared by the following method: 2,2-Dithiodibenzoic acid and acetic acid were evenly dispersed in a ratio of 0.05-0.1 g:50-80 mL, and then reacted at 70-90 °C for 10-14 h under vacuum conditions to obtain HIAM-JM.

3. The dichloromethane-resistant VOCs recovery organic membrane according to claim 1, characterized in that: The thickness of the intermediate layer is 70-80 μm, and the thickness of the active layer is 60-90 μm.

4. The dichloromethane-resistant VOCs recovery organic membrane according to claim 1, characterized in that: The average particle size of the hydrogen-bonded organic framework material is 30-50 nm.

5. The method for preparing a dichloromethane-resistant VOCs recovery organic film according to any one of claims 1 to 4, characterized in that: The steps include: The first coating liquid is applied on the base film, and after pre-drying, the second coating liquid is applied thereon, and then cross-linked at high temperature to obtain; The first coating liquid is prepared by the following method: ultrasonically oscillating a hydrogen-bonded organic framework material in n-heptane to obtain a HOF dispersion, and then uniformly mixing the HOF dispersion with a polybenzimidazole solution to obtain the first coating liquid; The second coating liquid is prepared by the following method: uniformly mixing a n-heptane solution of hydroxy vinyl silicone oil with a crosslinking agent and a catalyst to react, thereby obtaining the second coating liquid.

6. The preparation method according to claim 5, characterized in that: The temperature of the high temperature cross-linking is 120-140° C., and the time of the high temperature cross-linking is 4-6 hours.

7. The preparation method according to claim 5, characterized in that: In the preparation method of the first coating solution, the mass ratio of the hydrogen-bonded organic framework material to n-heptane is 2~10:90~98; the solvent of the polybenzimidazole solution is DMAc, and more preferably, in the polybenzimidazole solution, the mass ratio of polybenzimidazole to DMAc is 20~25:75~80; the mass ratio of the polybenzimidazole solution to the HOF dispersion is 5~10:90~95.

8. The preparation method according to claim 5, characterized in that: In the preparation method of the second coating liquid, the mass ratio of hydroxy vinyl silicone oil to n-heptane is 7~12:88~93; the mass ratio of the crosslinking agent to the n-heptane solution of hydroxy vinyl silicone oil is 1~4:6~9; and the catalyst is 0.01~1% by weight of the n-heptane solution of hydroxy vinyl silicone oil.

9. The preparation method according to claim 5, characterized in that: The cross-linking agent is tetraethoxysilane, and the catalyst is tetrabutyltin.

10. The preparation method according to claim 5, characterized in that: The base film is prepared by the following method: a solution of polyvinylidene fluoride is uniformly coated on a non-woven fabric, and then the base film is obtained through a phase inversion process.